Cryptocurrencies and their effects on the financial international system stability: Notes from Central America - Salas-Ocampo, Luis Diego (2022)
This research seeks to establish some of the implications for the stability of the international financial system of capital movements that occur in the context of the use of cryptocurrencies as legal tender and as an investment asset, trying to observe some specific lines for the Central American case. It addresses global entities of the international financial system, central banks of several continents and Central America. I makes evident the discourse and practices from a qualitative perspective using the discourse analysis technique which is combined with descriptive statistical analysis on the number of cryptocurrency owners in countries. It concludes that there is a relationship between the 2008 financial crisis and a very strong movement of the technical and computer sectors in the line of generating a whole process of reconceptualization and repositioning as financial consumers in the international and national financial system. In  addition, it visualizes three possible scenarios for resolving the tension between the private cryptocurrency instrumental sectors and international banking. On the other hand, it determines that in Central America there are no operational and technical conditions for the generation of Central Bank policies in relation to the incorporation of these in digital currencies.